Tragal Reconstruction After Tumor Excision. Issue 2 (February 2015) - Coombs, Christopher J.; Lin, Frank
Abstract : Abstract: The tragus forms a distinct and important landmark in the overall artistic and anatomical landscape of the ear. Despite its small size, it functions to cover and prevent direct access to the ear canal. Aesthetically, it has an important role in defining the morphology of the auricle in 3 dimensions, not only covering the meatus but also casting a shadow into the conchal bowl that gives the impression of depth. Most of the techniques for tragal reconstruction are associated with creation of a tragus in patients with microtia. We present here a new technique for tragal reconstruction in the setting of tumor ablation.